Special Metal-Alloy Coating and Catalysis - Wu, Wangping (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue will provide a snapshot of the state of the art in metals, alloy coatings, and films produced through several techniques, including PVD, CVD, MOCVD, electrodeposition, electroless, ALD, welding, etc. These metal and alloy coatings and films can act as corrosion and oxidation resistance barriers and catalysts to enable water splitting, among other catalysis applications. Ten contributions (nine articles and one review) have been published in this Special Issue, covering research topics such as the fracture of metal parts, progress in coating growth and characterization techniques, processing condition-structure-property relations, the development of novel lubricants and advanced simulations relevant to tribological contacts and metal manufacturing, and the structural, morphological, corrosion, oxidizing, wear, and catalytic properties of thin films. As the Guest Editor, I hope that the research results presented in this Special Issue will contribute to the further progression of research in the field of special metal alloy coating and catalysis.